MANAJEMEN BUDAYA SEKOLAH SEHAT DI SMK NEGERI 26 JAKARTA - Bedjo Sujanto; Supadi Supadi; Andreas Masa (PROCEEDING UMSURABAYA, 2022)
ABSTRACT This research was conducted to determine the planning, organization, implementation, and evaluation of healthy school culture at SMK Negeri 26 Jakarta. This study uses a qualitative method with a single case study design (explanatory). Data collection is done through observation, interviews, and documentation. The result of this research is that the principal does planning with weekly, monthly and yearly work meetings. The education work meeting which is held annually is attended by all section heads, school principals, and secretariats as well as coordinators. Furthermore, the principal selects several teachers to be assigned to the healthy school culture team once a year. The implementation of a healthy school culture is carried out by delivering, inculcating and practicing a healthy school culture through all subjects, programmed activities, habituation, and supporting activities to all school members. After the activity is carried out, the last step is to observe or monitor activities carried out by the teacher and focus on checking the suitability between plans and work instructions with the implementation of a healthy culture education program plan in schools.Keywords                   : Culture, Healthy School, Management